2015
DOI: 10.17221/7978-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for cold stress development in dairy cattle kept in free stall barn during severe frosts

Abstract: ABSTRACT:The impact of low temperatures combined with higher velocity of ventilated air in winter during severe frost in a free stall barn on the development of cold stress in Holstein-Friesian breed dairy cattle was studied. The study included measurements of outside and inside air parameters and cows' milk yield. Cold stress was evaluated in three technological groups (TG) using the WCT (Wind Chill Temperature) index. During the research, significant temperature and wind velocity differences (by up to 5°C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 14 publications
2
46
0
8
Order By: Relevance
“…According to Angrecka and Herbut (2015) only small decrease in milk production (1-2 kg) per day is present when cold stress in imminent. Cold weather and low temperature put, however, higher requirements on on quality and quantity of feed ration (Doležal and Černá, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to Angrecka and Herbut (2015) only small decrease in milk production (1-2 kg) per day is present when cold stress in imminent. Cold weather and low temperature put, however, higher requirements on on quality and quantity of feed ration (Doležal and Černá, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, for dairy cattle, the upper critical temperature at which thermal stress is manifested, according to , was determined to be +24 -27 °C [13]. found that the cold stress in dairy cows started manifesting itself as early as at 0 °C [14].…”
Section: Discussionmentioning
confidence: 99%
“…Кожна зміна умов навколишнього середовища викликає деяке порушення життєвої рівноваги тварин, змушуючи їх пристосовуватися до цих змін. Здатність корів протистояти цим змінам залежить від видових, породних, вікових і технологічних відмінностей (Adamczyk et al, 2011;Angretska & Herbut, 2015;Herbut, 2013;Toušová et al, 2017;Tsyupko et al, 1995). Метою досліджень було вивчення продуктивності, добової поведінки та біоенергетичної оцінки корів української червоно-рябої молочної породи за різних варіантів безприв'язного утримання у різні періоди температурного навантаження.…”
Section: вступunclassified
“…Погодно-кліматичні умови є важливою складовою правильної організації утримання худоби та суттєво впливають на реалізацію її продуктивного потенціалу (Angretska & Herbut, 2015;Herbut & Angretska, 2013). Результати досліджень показали, що зниження температури навколишнього середовища спричинило зменшення продуктивності корів та незначне підвищення масової частки жиру в молоці за обох варіантів утримання (табл.1).…”
Section: результати дослідженняunclassified